2015
DOI: 10.1177/229255031502300108
|View full text |Cite
|
Sign up to set email alerts
|

Isolated limb infusion: Efficacy, toxicity and an evolution in the management of in-transit melanoma

Abstract: Background Isolated limb infusion (ILI) delivers low-flow chemotherapy via percutaneous catheters to treat melanoma in-transit metastases. Objective To describe the experience of two regional referral centres with ILI. Methods A retrospective review of patients who underwent ILI between 2002 and 2012 was performed. Outcomes were measured using the WHO criteria for response, the Wieberdink toxicity score and long-term limb function using the Toronto Extremity Salvage Score (TESS). Results Fifty-two patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It has been further observed that there is no study focusing on predicting the outcomes of limb perfusion. All of the studies are on the contribution of perfusion to OS and disease-free survival (DFS) [ 10 , 19 ]. Therefore, this is the first study in this regard as the systemic inflammatory response is utilized and is a two-step study.…”
Section: Dıscussıonmentioning
confidence: 99%
“…It has been further observed that there is no study focusing on predicting the outcomes of limb perfusion. All of the studies are on the contribution of perfusion to OS and disease-free survival (DFS) [ 10 , 19 ]. Therefore, this is the first study in this regard as the systemic inflammatory response is utilized and is a two-step study.…”
Section: Dıscussıonmentioning
confidence: 99%
“…The ILI literature was searched to identify all studies in which the primary outcome was the ORR of patients with limb melanoma following melphalan ILI (Table 1) [29,30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Some centres also used actinomycin D. Not all centres used hyperthermia.…”
Section: Isolated Limb Infusionmentioning
confidence: 99%